Selection and Application of Bacteriophages for Treating Salmonella enteritidis Infections in Poultry - Higgins, S.E.; Higgin, J.P.s; Bielke, L.R.; Hargis, B.M. (International Journal of Poultry Science, 2007)
The objective of this study was to select appropriate bacteriophages that survive in the gastrointestinal tract of neonatal poultry and utilize those bacteriophages to reduce intestinal colonization of Salmonella enteritidis phage type 13A (SE) in challenged birds. Broiler chicks served as an in vivo biological filter to preferentially select bacteriophages from our bacteriophage library capable of surviving the gastrointestinal environment. A mixture of bacteriophage isolates designated PHL 1-71 was administered orally to three SE challenged chicks on three consecutive days. Each day, bacteriophages were recovered from the ileum, ileocecal junction and ceca for sequential administration the following day. The recovered bacteriophages were then administered to SE-infected turkey poults. In the first experiment, two-day old poults were challenged with 104cfu SE and treated 48 h later with 5mM Mg (OH)2 followed by 2.5×109 plaque forming units (pfu) of bacteriophages in 1mM Mg (OH)2 solution. This treatment numerically reduced SE recovered from cecal contents at 12 and 24 h after treatment as compared to untreated controls. In a second experiment, two-day old poults were challenged with 1.6×104 cfu SE and treated with 5mM Mg (OH)2 followed by 7.5×109 pfu phage in 1mM Mg (OH)2 solution 48 h post-challenge. We recovered 79,728 cfu of SE per g of cecal contents in the control group and 11,224 cfu/g in the phage treated group 24 h post treatment. These data were not significantly different, but they suggest that bacteriophages can be preferentially selected in vivo to increase survival in the avian gastrointestinal tract. However, improved efficacy is required prior to useful application of the approach for reducing Salmonella infection.